2018
DOI: 10.5951/jresematheduc.49.4.0462
|View full text |Cite
|
Sign up to set email alerts
|

Five Decades of Mathematics Education Research

Abstract: Mathematics educators have been publishing their work in international research journals for nearly 5 decades. How has the field developed over this period? We analyzed the full text of all articles published in Educational Studies in Mathematics and the Journal for Research in Mathematics Education since their foundation. Using Lakatos's (1978) notion of a research programme, we focus on the field's changing theoretical orientations and pay particular attention to the relative prominence of the experimental p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 36 publications
4
59
0
Order By: Relevance
“…groups of experts” (Lee & Martin, 2015, p. 21). The specific text analysis tool we will use is called topic modeling, a tool that Inglis and Foster’s (2018) map of math education rightly described as analogous to a quantitative version of grounded theory.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…groups of experts” (Lee & Martin, 2015, p. 21). The specific text analysis tool we will use is called topic modeling, a tool that Inglis and Foster’s (2018) map of math education rightly described as analogous to a quantitative version of grounded theory.…”
Section: Methodsmentioning
confidence: 99%
“…The analogy between topics and grounded theory is particularly insightful when we recognize that in topic models, “there are no preconceived ideas about the topics that will emerge” (Inglis & Foster, 2018, p. 470). Topics are the result of iterative learning steps: Our model learns the mixture of topics that make up each document and the words that belong to each topic via successive updates to two sets of prior multinomial distributions, one of documents over topics and one of topics over words.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Topic modelling has been used to analyse newspaper coverage of nuclear technology (Jacobi et al, 2016) and messages from social networks, such as Facebook (Hong & Davison, 2010). It has also been applied to journal articles in research fields (Paul & Girju, 2009); in mathematics education, we have used topic modelling to analyse the content of leading international research journals (Inglis & Foster, 2018).…”
Section: Topic Modellingmentioning
confidence: 99%
“…Mathematics Education has oriented its efforts, mainly, to the study of factors affecting mathematics teaching and learning processes, attending to the plurality of contexts, demands, and social needs, as well as scientific progress. Thus, both the problems and research agendas (Behr et al, 1984;Howson, 1988;Long, Meltzer, & Hilton, 1970;Skovsmose, 2012;Wheeler et al, 1984;Wilson, 2020) that have been identified and addressed in the research in Mathematical Education have evolved depending on the educational reforms and changes in educational paradigms generated by such needs (Artigue, 1998;Inglis & Foster, 2018;NCTM Research Committee, 2015). Inglish and Foster (2018) identified 'turns of interest' in the recent history of Mathematics Education, in topics such as geometry, calculators, programming, computers, and others.…”
Section: Introductionmentioning
confidence: 99%